Os impactos financeiros dos restos a pagar na execução orçamentária e financeira das IFES da região Centro-Oeste no período de 2008 a 2016 - Vasconcelos, Cássia Cardoso de Carvalho (2018)
The object of study of this research is expenses classified as carryovers, which are part of the public budget, and they are a challenge for public managers. The objective of the research is to propose a control instrument applicable to the budgetary and financial execution of an IFES, considering the legislation applicable to the public budget, that assists the manager in controlling and reducing the effects of expenses classified as carryovers. Descriptive analysis and application of Pearson's correlation index were carried out on data taken from the Federal Government's Portal, referring to the five universities in the Center-West region between 2008 and 2016. It is concluded that: carryovers are present in all universities evaluated; on average, more than a quarter of the budget started is not finalized in the same year; unprocessed leftovers account for more than 90% of the total unpaid debts of universities. Furthermore, it is found that: there is a moderate negative correlation to budget execution and unbundling of UNB; there is a moderate positive correlation between the remainders to be paid and the financial execution of the budget in the UFGD and the UNB, and negative correlation in the UFG. The intervention proposal has two stages: the first one is the collection of information on the budgetary and financial situation of IFES, through a control sheet, and the second step is the application of the GUT matrix in the budget balances of the carryovers, to prioritize the closure of such expenses.